Sustainable regenerative agriculture allied with digital agri-technologies and future perspectives for transforming Indian agriculture - Sharma C.; Pathak P.; Kumar A.; Gautam S. (My University, 2025)
The agriculture industry is facing a difficult situation as an outcome of mounting food demand, food security, climatical situations, legislative laws, etc. Moreover, the practice of chemical fertilizer in agriculture adds to greenhouse gas emissions and large water consumption. As a result, agricultural systems must be rethought to become more robust and sustainable. Regenerative agriculture, a collection of agricultural methods and techniques that prioritize long-term organic farming, environmental responsibility, and sustainability, is a potential solution to these issues. This review intends to discuss the interplay between regenerative agriculture (RA) and digital agri-technologies to attain sustainability. The significance of RA over conventional agri-technologies, the role of nanobiotechnology, smart sensors, and other fourth Agri-tech 4.0 innovations to augment food production are emphasized. Growing evidence shows that digital technologies (particularly the Internet of Things (IOTs), big data, artificial intelligence, and blockchain) would have a greater impact on RA. These practices can have an array of environmental benefits. Precision agri-technologies like internet-of-things (IoTs), cloud computing, blockchain, satellites, drones, use of nanosensors, and remote sensing of fresh produce during the supply chain can augment food production at a commendable rate. Implementation of automated harvesting processes to attain minimum contact harvesting and post-harvest operations are quite useful in increasing food production. Thus, current strategies toward agricultural transformation and novel government policies, toward sustainable regenerative agriculture could be a game-changer in sustainable agriculture. These implications are derived through carefully analysing the published literature we have amassed using various search engines. However, more research is still needed to entirely harness the benefit of progressive technologies, to realize a healthier and further sustainable agriculture future. © The Author(s), under exclusive licence to Springer Nature B.V. 2024.